Cardiomyocyte-Specific RIP2 Overexpression Exacerbated Pathologic Remodeling and Contributed to Spontaneous Cardiac Hypertrophy - Yang, Jing-jing; Zhang, Nan; Zhou, Zi-ying; Ni, Jian; Feng, Hong; Li, Wen-jing; Mou, Shan-qi; Wu, Hai-ming; Deng, Wei; Liao, Hai-han; Tang, Qi-zhu (Frontiers in Cell and Developmental Biology, 2021)
This study aimed to investigate the role and mechanisms of Receptor interacting protein kinase 2 (RIP2) in pressure overload-induced cardiac remodeling. Human failing or healthy donor hearts were collected for detecting RIP2 expression. RIP2 cardiomyocyte-specific overexpression, RIP2 global knockout, or wild-type mice were subjected to sham or aortic banding (AB) surgery to establish pressure overload-induced cardiac remodeling in vivo. Phenylephrine (PE)-treated neonatal rat cardiomyocytes (NRCMs) were used for further investigation in vitro. The expression of RIP2 was significantly upregulated in failing human heart, mouse remodeling heart, and Ang II-treated NRCMs. RIP2 overexpression obviously aggravated pressure overload-induced cardiac remodeling. Mechanistically, RIP2 overexpression significantly increased the phosphorylation of TAK1, P38, and JNK1/2 and enhanced IκBα/p65 signaling pathway. Inhibiting TAK1 activity by specific inhibitor completely prevented cardiac remodeling induced by RIP2 overexpression. This study further confirmed that RIP2 overexpression in NRCM could exacerbate PE-induced NRCM hypertrophy and TAK1 silence by specific siRNA could completely rescue RIP2 overexpression-mediated cardiomyocyte hypertrophy. Moreover, this study showed that RIP2 could bind to TAK1 in HEK293 cells, and PE could promote their interaction in NRCM. Surprisingly, we found that RIP2 overexpression caused spontaneous cardiac remodeling at the age of 12 and 18 months, which confirmed the powerful deterioration of RIP2 overexpression. Finally, we indicated that RIP2 global knockout attenuated pressure overload-induced cardiac remodeling via reducing TAK1/JNK1/2/P38 and IκBα/p65 signaling pathways. Taken together, RIP2-mediated activation of TAK1/P38/JNK1/2 and IκBα/p65 signaling pathways played a pivotal role in pressure overload-induced cardiac remodeling and spontaneous cardiac remodeling induced by RIP2 overexpression, and RIP2 inhibition might be a potential strategy for preventing cardiac remodeling.